Ecological niche and phenotypic differences among two alpine Rhododendron species and their natural hybrids in a common landscape - Yanghui Zhao; Ying Zhang; Liang Xu; Yadan Yan; Chuncheng Wang; Yafeng Wen; Donglin Zhang (Global Ecology and Conservation)
Species sharing an environment face similar selective pressures, often evolving adaptive divergence traits to reduce competition. Quantifying ecological niche and phenotypic traits among sympatric species is crucial for understanding ecologically moderated biodiversity. We integrate ecological and phenotypic datasets to investigate the extent to which three sympatric alpine Rhododendron species in the mountainous southwest of China (parents: Rhododendron delavayi and R. irroratum; natural hybrid: R. agastum) differed in their adaptations to co-exist in a shared environment. We utilized principal component analysis, one-way analysis of variance, and niche-identity tests to summarize and compare environmental and phenotypic divergence. Leaf phenotypic traits related to structure, morphology, biomass, and physiology were analyzed, as they were key indicators of niche and phenotypic differences, crucial for the co-existence of sympatric Rhododendron species. We employed nested linear models, and phenotypic differentiation coefficients to assess inter- and intraspecific phenotypic variation. Pearson's correlation analysis and Mantel tests identified key environmental factors influencing leaf phenotypic variation. The results indicate that the three Rhododendron species exhibit different preferences for environmental factors such as annual mean temperature, temperature seasonality, annual precipitation, water vapor pressure, and soil organic matter. These distinct ecological preferences may represent specific ecological adaptations that facilitate their coexistence in sympatry. Leaf area, leaf length, leaf thickness, and leaf tissue density emerged as key indicators for distinguishing the leaf phenotypes of the three Rhododendron species. Elevation, temperature, and precipitation-related factors are significantly correlated with leaf phenotypic variation. The observed ecological niche and phenotypic differences observed likely resulted either causal effects or indirect consequences of ecologically mediated changes. Our study offered novel insights into the mechanisms underlying evolutionary versatility and ecological success among sympatric species.